2019
DOI: 10.3390/su11082377
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Business Strategy and Inventory on the Relationship between Sales Manipulation and Future Profitability

Abstract: Many researchers have found that real activities manipulation undermines future profitability, because it deviates from normal operating activities. We are interested in sales manipulation, which is one type of real activities manipulation relating to corporate sustainability. First, we empirically examine whether the effects of sales manipulation on future profitability differ according to the strategies of a firm. Next, we divide sales manipulation as a type of real activities manipulation and optimal sales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This suggests that the company should enhance its utilization of assets to generate more revenue. Companies have the opportunity to boost their ROA by increasing their profit margin through strategies such as product differentiation or by improving asset turnover using a cost leadership strategy [43]. This research also found that the goal of minimizing the operating ratio has not been achieved.…”
Section: Discussionmentioning
confidence: 82%
“…This suggests that the company should enhance its utilization of assets to generate more revenue. Companies have the opportunity to boost their ROA by increasing their profit margin through strategies such as product differentiation or by improving asset turnover using a cost leadership strategy [43]. This research also found that the goal of minimizing the operating ratio has not been achieved.…”
Section: Discussionmentioning
confidence: 82%
“…If firms properly maintain inventory then any manipulation in sales give rise to future profitability and firms' position. Due to minimisation of inventory holding cost and obsolescence is having indirect effect on firms' performances (Yi et al, 2019).…”
Section: Inventory Automation Practices and Firms Productivitymentioning
confidence: 99%
“…al. [10], and Yi et al [11], business development in MSMEs [12], business development strategy [13]. However, there is a lack of research discussing strategy innovation for increasing sales, especially in Streetwear MSMEs.…”
Section: Introductionmentioning
confidence: 99%